Thiourea-formaldehyde polymer a new and effective corrosion inhibitor for mild steel in hydrochloric acid solution - Singh P.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
Thiourea-Formaldehyde polymer (T-F Polymer) was synthesized by microwave method and its inhibitive action on the corrosion of mild steel (MS) in 1 M HCl was investigated under different experimental conditions using weight loss, electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization technique. These techniques confirmed the adsorption of polymer on mild steel surface. Results obtained showed that the polymer acts as a good corrosion inhibitor for MS in 1 M HCl. It inhibits corrosion by adsorption mechanism. Tafel polarization data revealed that the polymer acted as mixed-type inhibitor. The adsorption of the inhibitor on mild steel surface obeyed the Langmuir adsorption isotherm. © 2014 The Authors.